Alignment of Patient Health Numeracy with Asthma Care Instructions in the Patient Portal - Marilyn M. Schapira; Chantel Mozal; Frances S. Shofer; Rodalyn Gonzalez; Andrea J. Apter (SLACK Incorporated, 2017)
Background: After Visit Summary (AVS) instructions provided through the patient portal of the electronic medical record can support asthma self-management if patients have the skills to interpret and apply the health information provided. Print literacy demands of patient materials are often higher than the reading ability of patients. However, less is known regarding the numeric demand of patient education materials and how well it aligns with patient health numeracy. Objectives: This study (1) developed measures of numeric demand for use in the AVS, (2) described the health numeracy demand of AVS instructions for asthma care, and (3) evaluated the association between numeracy demand of materials and patient health numeracy. Methods: We reviewed personalized AVS instructions for an index visit from 74 adults with moderate or severe asthma recruited from clinics serving low-income urban communities. Using measures of numeric complexity and density developed for this study, numeracy demand of the AVS was compared to the numeracy skills of patients using the validated Asthma Numeracy Questionnaire. Key Results: The numeric complexity and density scales demonstrated content and face validity. The median (range) of the numeric complexity score for AVS instructions was 2.5 (0-46), and density of numeric information was 8% (0%-33%). The median (range) of the Asthma Numeracy Questionnaire was 2 (0-4). There was no association between patient asthma-related health numeracy and the complexity (p = .29) or density (p = .81) of numeric information. Conclusions: Patient instructions regarding medications and self-management often include numeric information. Lack of alignment of the numeracy demand of materials with health numeracy skill may be a barrier to communication, particularly among patients of lower health numeracy.